Microstructure evolution and deformation mechanisms of service-exposed P91 steel via interrupted uniaxial creep tests at 660 °C - R. Bonetti; N.C. Neate; A. Morris; P.H. Shipway; W. Sun (Journal of Materials Research and Technology)
Creep degradation behaviour of service-exposed P91 steel is evaluated during interrupted creep tests at 660 °C and 80 MPa using a number of material characterization techniques including transmission electron microscopy (TEM), scanning electron microscopy (SEM), electron backscattered diffraction (EBSD), energy dispersive spectroscopy (EDS) and optical microscopy (OM) to identify the microstructural evolution and the associated deformation mechanisms. Microhardness has also been measured in order to evaluate the softening mechanism. Under the creep conditions examined, microstructural degradation is found to be governed by the disappearance of the lath sub-structure, lath widening and recrystallization, as well as dislocation density reduction, coarsening of M23C6 and creep cavitation while MX and Laves phases are stable. Hardness evolution, extrapolated from hardness data obtained from uniaxial creep tests, is used to characterize the softening of the material. On this basis, hardness decrease is justified in term of the aforementioned microstructural changes. Implications of the findings for specific in-service life management in thermal plant piping systems are addressed.